Miscellaneous electric loads in tropical buildings - an opportunity for energy conservation improvement. - Kwong, Qi Jie; Adam, Nor Mariah; Goh, Sind Hoi; Raghavan, Vijay R. (2012)
The small plug loads, or the Miscellaneous Electric Loads (MELs) in the tropical buildings typically account for up to 30% of the total electricity usage and is expected to rise in the near future. However, as compared to other energy consuming building systems, less attention has been paid to the MELs due to its elusive, more diversified and sophisticated nature. This study aims to identify the opportunity of energy efficiency improvement of the MELs in an institutional building in Malaysia, by focusing on the user behavioural action and power management features of equipment towards potential energy savings. The results obtained show that about 19% of the total energy demand can be reduced if all of the users turned off, unplugged or disconnected the office equipment when not required, and this lead to a significant reduction in greenhouse gases emission. This finding is particularly important for good energy demand management, as more and more modern electric appliances are introduced into the local commercial buildings which are contributing to the increase in energy consumption and subsequently, the utility bill.